XML And Related Technologies. - Atul, Kahate (1900)
XML has become the standard for all kinds of integration and deployment of applications, regardless of the technology platform. This book covers all aspects of dealing with XML, both from a conceptual as well as from a practical point of view. The book follows a visual approach to introduce concepts, making understanding it very easy. A large number of case studies and examples are provided for ease of learning and for hands-on practice.
Set Up for Running XSL-FO Examples -- Creating Lists in XSL-FO -- Key Terms and Concepts -- Chapter Summary -- Practice Set -- XML and Java -- Basics of Parsing -- What is Parsing? -- Parsing Approaches -- The StAX API -- JAXP -- Sun's JAXP -- JAXP and SAX -- JAXP and DOM -- JAXP and StAX -- XML and JAVA - A Case Study -- Case Study -- Key Terms and Concepts -- Chapter Summary -- Practice Set -- XML and ASP.NET -- Introduction -- XMLReader -- XMLWriter -- Extracting Data from a Database as an XML Document -- Key Terms and Concepts -- Chapter Summary -- Practice Set -- Web Services and AJAX -- Web Services -- Introduction -- How are Web Services Different? -- The Buzzwords in Web Services -- Java Web Services -- RESTful Web Services -- AJAX -- Introduction -- How does AJAX work? -- AJAX FAQ -- Life Without AJAX -- AJAX Coding -- Role of XML in Ajax - Case Study -- Key Terms and Concepts -- Chapter Summary -- Practice Set -- XML Security -- Introduction -- Threats and Risks -- Cryptography -- Symmetric and asymmetric key Cryptography -- Symmetric key Cryptography -- Asymmetric key Cryptography -- The RSA Algorithm -- Digital Signature -- XML Security -- XML Encryption -- XML Digital Signature -- XML key Management Specification -- Key Terms and Concepts -- Chapter Summary -- Practice Set -- Appendix - Miscellaneous Topics -- XML and Javascript -- VoiceXML -- XML and Databases -- Security Assertion Markup Language -- How SAML Works? -- classification of Assertions -- Assertion Details -- Assertion Examples -- ODF Versus OOXML -- Standardisation and Protocols -- JSON - An Alternative to XML? -- JSON Benefits -- JSON Technical Details -- JSON Drawbacks -- XHTML - The New HTML Standard -- XHTML Document Types -- Benefits of XHTML -- The W3C Markup Validation Service -- Valid XHTML -- invalid XHTML -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books